Agriculture urbaine et souveraineté alimentaire à Genève (Suisse), machines à consentement ou moteurs d’hybridation du référentiel agricole dominant ? - Rémi Schweizer; Cyril Mumenthaler (VertigO)
While they have long been considered as initiatives emanating from civil society or peasant movements, urban agriculture and food sovereignty are now integrated in policy design and instruments. On the one hand, alternative food movements actively seek to reach broader decision-making spheres. On the other hand, public authorities and private actors increasingly refer to such notions to guide or justify their action. The article questions the impacts of these trends from two main perspectives : their effect on the power relations between actors ; and their transformative potential, that is their capacity to alter a sectorial frame of reference driven by market and multi-functionality logics. The demonstration relies on a case study located in Geneva, Switzerland, concerned with the development of the regional brand Genève Region - Terre Avenir (GRTA). This case is interesting for three reasons : the close (and explicit) link to urban agriculture and food sovereignty, the collaborative forms of governance that have been developed in a country where the agro-food sector has long been considered as strongly corporatist, and the criteria of guarantee (quality, proximity, traceability and fairness) that distinguish GRTA from comparable brands. These singularities are explored through a cognitive approach, which considers change as the result of a confrontation between communities of actors whose belief systems diverge. Throughout the case study, compromises and imbalances between communities are highlighted. In the end, the difficulties to upset the dominant frame of reference are underlined.